Impact of Learner-Centred Teaching Environment with the Use of Multimedia-mediated Learning Modules in Improving Learning Experience - Yap, Wei Li (Penerbit UTM Press, Universiti Teknologi Malaysia., 2014)
Malaysian tertiary education is still very much practicing the traditional teaching and learning approach. There had been a push by the Ministry of Education in Malaysia to move towards outcome-based education. Technology can be used to facilitate teaching and learning process moving towards outcomebased education. The use of technology can help forming learner-centred teaching environment where in this research students were exposed to online learning environment through the Internet platform and it was also known as a self-directed learning environment. Besides online platform, multimedia technology can be used to help enhance students’ learning experience by motivating them to learn. This research allowed students to have independent learning using multimedia learning module. With the aid of technology used in education, learner-centred teaching could be formed. Learner-centred teaching allowed the focus to be shifted from lecturers to students, and then learner understanding and motivation would be improved. This research was conducted using mixed-method research design. Results from pre/post-tests, survey and students’ comments were triangulated and indicated that learner-centred teaching environment with the use of multimedia-mediated learning module contributed in improving learner motivation compared to teachercentred teaching environment. This research supported the benefits of shifting from teacher-centred teaching to learner-centred teaching environment.